Comparison between the prevalences of herpes simplex virus type 1 and 2 among Libyan women with spontaneous abortion in Ajdabiya city - Souad Issa Rashwan (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
Herpes simplex virus (HSV) is a significant human pathogen that causes various infections such as genital herpes. Infection during pregnancy poses a significant risk to pregnant women, primarily affecting outcomes such as miscarriage. High seroprevalence of HSV-1 and HSV-2 is observed globally, with significant differences across countries. So aims of this study to compare between infections of two types of herpes simplex virus among women with unexplained spontaneous abortion in Ajdabiya city, eastern Libya, in terms of prevalence, severity, immune responses, and assess related risk factors critical to better managing the infection. Methods: Blood samples were collected from 60 Libyan women with unexplained spontaneous abortion aged 19 to 48 years, attributed to the central hospital of Ajdabiya, Serum was separated then analysed using HSV 1-IgG/IgM and HSV 2-IgG/IgM, a lateral flow chromatographic immunoassay. The results obtained were processed in SPSS Version 25. Results of 23.3% and 35% of total cases were seropositive for IgM of HSV1 and HSV2, respectively, while 83.3% and 6.7% were seropositive for IgG of HSV1 and HSV2, respectively. There was a weak positive correlation between the occurrence of acute infections of HSV1 and HSV2 (P=0.048, R=0.258), while there was no significant correlation between past infections of HSV1 and HSV2 (P=0.363). Conclusion: Herpes simplex virus type 2 is more prevalent than type 1 , suggesting that HSV-2 is more severe than HSV-1. A significant low seropositivity of HSV-2 IgG was found, in contrast to HSV-1, suggesting that HSV-2 is better able to evade the immune system than HSV-1. This highlights the need for informing women and their partners about herpes transmission, early symptoms, and preventive measures.